MODEL PEMBERDAYAAN KOMITE SEKOLAH DALAM IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DENGAN MEMBANGUN JARINGAN KAPITAL SOSIAL - Tri Suminar; Mintarsih Arbarini; - Utsman (Universitas Negeri Semarang, 2010)
The school committee, school principal and teachers are the key role in schools that implement school-based management. This research aims to develop a model of empowerment of school committees in the implementation of school-based management by developing networks of social capital.This research uses research and development approach with the school committee members and all components of the school as the subjects. The interview records and documents are analyzed qualitative-descriptivephenomenologycallyand inferential statistically. The finding is the performance of the school committee is still not good. This is caused by the lack of cooperation between school committee and school component. There are no bound by norms of solidarity and trust among them to carry out school management. School committees empowerment by establishing effective networks of social capital, effectively improves school comitteÃ¢â‚¬Å¸s performance by 13.75 points. There are consistent changes between social capital intensity and qualification performance of the school committee. The school committee should behave and act proactively, and also more creative to foster the trust of the school. Keywords: school-based management, empowerment, school committees, social capital.